The use of array-CGH in a cohort of Greek children with developmental delay - Eleftheriades Makarios; Tsoplou Panagiota; Vasileiadis Lefteris; Kitsos George; Garas Antonios; Louizou Eirini; Rapti Stamatia-Maria; Kefalas Konstantinos; Vetro Annalisa; Manolakos Emmanouil; Peitsidis Panagiotis; Orru Sandro; et al. (Molecular Cytogenetics, 2010)
Abstract Background The genetic diagnosis of mental retardation (MR) is difficult to establish and at present many cases remain undiagnosed and unexplained. Standard karyotyping has been used as one of the routine techniques for the last decades. The implementation of Array Comparative Genomic Hybridization (array-CGH) has enabled the analysis of copy number variants (CNVs) with high resolution. Major cohort studies attribute 11% of patients with unexplained mental retardation to clinically significant CNVs. Here we report the use of array-CGH for the first time in a Greek cohort. A total of 82 children of Greek origin with mean age 4.9 years were analysed in the present study. Patients with visible cytogenetic abnormalities ascertained by standard karyotyping as well as those with subtelomeric abnormalities determined by Multiplex Ligation-dependent Probe Amplification (MLPA) or subtelomeric FISH had been excluded. Results Fourteen CNVs were detected in the studied patients. In nine patients (11%) the chromosomal aberrations were inherited from one of the parents. One patients showed two duplications, a 550 kb duplication in 3p14.1 inherited from the father and a ~1.1 Mb duplication in (22)(q13.1q13.2) inherited from the mother. Although both parents were phenotypically normal, it cannot be excluded that the dual duplication is causative for the patient's clinical profile including dysmorphic features and severe developmental delay. Furthermore, three de novo clinically significant CNVs were detected (3.7%). There was a ~6 Mb triplication of 18q21.1 in a girl 5 years of age with moderate MR and mild dysmorphic features and a ~4.8 Mb duplication at (10)(q11.1q11.21) in a 2 years old boy with severe MR, multiple congenital anomalies, severe central hypotonia, and ataxia. Finally, in a 3 year-old girl with microcephaly and severe hypotonia a deletion in (2)(q31.2q31.3) of about ~3.9 Mb was discovered. All CNVs were confirmed by Fluorescence in situ hybridization (FISH). For the remaining 9 patients the detected CNVs (inherited duplications or deletions of 80 kb to 800 kb in size) were probably not associated with the clinical findings. Conclusions Genomic microarrays have within the recent years proven to be a highly useful tool in the investigation of unexplained MR. The cohorts reported so far agree on an around 11% diagnostic yield of clinically significant CNVs in patients with unexplained MR. Various publicly available databases have been created for the interpretation of identified CNVs and parents are analyzed in case a rare CNV is identified in the child. We have conducted a study of Greek patients with unexplained MR and confirmed the high diagnostic value of the previous studies. It is important that the technique becomes available also in less developed countries when the cost of consumables will be reduced.